Overview of Athlete Blood Profile and Fitness Level of Adolescent Basketball Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to provide an overview of the blood profile and fitness levels of adolescent basketball athletes at Old School Makassar and to assess the relationship between these physiological parameters. The study used a cross-sectional design with a total sampling of athletes aged 13–16 years who actively participate in regular training. Blood profile examinations included measurements of hemoglobin levels and random blood sugar levels conducted before the fitness test. The fitness test included a 20-meter sprint and a multistage shuttle run used to calculate the estimated VO₂max as an indicator of aerobic capacity. The results showed that the average hemoglobin level of athletes was within the normal range, namely 14.17 g/dL, while the average random blood sugar was 94.8 mg/dL. The average VO₂max of 45.3 ml/kg/min indicates a good fitness category for the adolescent age group. Descriptive analysis showed a tendency that athletes with higher hemoglobin levels and stable blood sugar levels had better fitness performance, especially in VO₂max achievement and shuttle run results. These findings indicate that hematological and metabolic profiles play an important role in supporting the physical abilities of adolescent athletes. Regular monitoring of hemoglobin and random blood sugar can help coaches design more targeted training programs and identify potential risks of fatigue or metabolic imbalance. Overall, this study underscores the importance of comprehensive physiological evaluation as part of the performance coaching and fitness development of youth basketball athletes.